Recent trends in vaccine coverage and confidence: A cause for concern - Rachel L. Eagan; Heidi J. Larson; Alexandre de Figueiredo (Taylor & Francis Group, 2023)
Declining trends in vaccine confidence come at a time when routine immunization coverage for children has slumped to a decades-long low. With some of the largest losses in confidence experienced among young adults, this is a concerning trend with the potential for long-term implications. This article reflects on recent research examining the levels and trends of vaccine confidence over time and across the globe, the drivers influencing confidence, and the role of the COVID-19 pandemic in shaping confidence today. Timely examination of the causes and consequences of waning vaccine confidence and critical evaluation of COVID-19 response measures will prove vital in mitigating additional losses in vaccine confidence and uptake while contributing to building resilience in the face of future health crises.